2012
DOI: 10.1111/j.1469-0691.2011.03478.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of carbapenem resistant Klebsiella pneumoniae bloodstream infections

Abstract: The aim of this study was to evaluate the impact of carbapenem-resistant K. pneumoniae bloodstream infections on mortality. During the study period 42, 68 and 120 patients were identified with carbapenem-resistant, extended-spectrum β-lactamase producers (ESBL) and susceptible K. pneumoniae bloodstream infections, respectively. Patients with carbapenem-resistant K. pneumoniae had higher rates of prior antimicrobial exposure, other nosocomial infections, and use of invasive devices. Infection-related mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
233
9
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(275 citation statements)
references
References 33 publications
17
233
9
10
Order By: Relevance
“…Several reports have shown that carbapenem resistance was independently associated with an increase in mortality [21][22][23]. In our study, attack mortality rate was significantly higher in patients infected with carbapenem-resistant strains.…”
Section: Discussionsupporting
confidence: 57%
“…Several reports have shown that carbapenem resistance was independently associated with an increase in mortality [21][22][23]. In our study, attack mortality rate was significantly higher in patients infected with carbapenem-resistant strains.…”
Section: Discussionsupporting
confidence: 57%
“…Kan dolaşımı sistemi enfeksiyonlarının tedavisinde çoğul dirençli mikroorganizmalardan özellikle GSBL üretenler sorunlar oluşturmaktadır (4,(21)(22)(23). Karbapenemler GSBL üreten ve çoğul dirençli mikroorganizmaların tedavisinde en etkili antibiyotikler olmasına rağmen sık kullanımları durumunda bunlara karşı da direnç gelişimi oluşmaktadır (22,24,25). Çalışmamızda Acinetobacter spp.…”
Section: Discussionunclassified
“…Komorbiditäten wurden in etlichen Studien als signifikante Risikofaktoren gefunden [183,186,[188][189][190]. Daneben fanden sich eine kürzliche Organtransplantation [198], vorhergehende Operationen [185,190] oder nicht operative Eingriffe [189], zentrale Gefäßzugän-ge [183,187,189,198], mechanische Beatmung [185,190,198], Magensonden [187,190], Harnwegskatheter [187,189], Wunden [187], Aufenthalt auf Intensivstationen [183,185,187,189,198], vorhergehende Hospitalisierung [189] und die Dauer des Krankenhausaufenthaltes [183,187,190,198] [140]. Auf 16 deutschen Intensivstationen entwickelten 10 % der Patienten, die mit 3.…”
Section: Neben Patienteneigenenunclassified
“…In einer anderen Studie fand sich bei 26 % aller Patienten mit positiver S urveillance-Kultur im weiteren Verlauf eine positive mikrobiologische Probe und zwar im Median neun Tage nach der Surveillance-Kultur [183].…”
Section: Effektivität Von Aktiver Surveil Lanceunclassified